Perbedaan Tingkat Adiksi Games Online pada Remaja Ditinjau dari Pola Asuh Orang Tua - Azizah, Nur; Putra, Achmad Irvan Dwi; Lawrence, Wynnie; Fongusen, Chelsea; Naibaho, Elisabetta; Karan, S. Sanjay (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2019)
Abstract.The ease of accessing online games tend to make players interested in lingering in front of the computer and forgot about other activities. This could be impact on the psychology self-development, if online games were played without rules and uncontrolled. Therefore, it was important for parents to always control and supervise their children strickly while playing online games. Related to each parenting styles which have their own impact to children, this research aims to discover the differences of online games addiction viewed from parenting styles of the second grade student in Junior High School in Sultan Iskandar Muda Medan. The hypothesis in this study state that there was a significant differentation among online games addiction with parenting styles. In this study, the sampling technique using purposive sampling, which amounted to 203 research subjects on first and second grade of junior high school. The data collected by the scale of online games addiction and parenting styles. The calculation was performed by assumption test which consists normality and homogeneity test. Data was analyzed with One Way ANAVA on SPSS 19 for Windows. The results showed that the sig = 0,000 0,05. So it can be concluded that the hypothesis is acceptable.Keywords: games online addiction; parenting styles; teenagersÂ Copyright Â© 2019. Pusat Penelitian dan Layanan Psikologi.